ANALISIS TINDAK TUTUR ILOKUSI DALAM ACARA MAMANU-MANU PERNIKAHAN MASYARAKAT BUGIS DI KAMPUNG LAUT TANJUNG JABUNG TIMUR - Rika Julianti; Andiopenta Purba; Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aims to describe the forms and functions of illocutionary speech acts used in the Mamanu-manu ceremony of Bugis marriage in Kampung Laut, Tanjung Jabung Timur. Mamanu-manu is the initial stage carried out by the male family to convey their intention to propose to the female family through a formal dialogue between representatives of both parties. This study employed a pragmatic approach with a descriptive qualitative method. The data were obtained from utterances spoken by the speakers (pa’bicara) and the interlocutors (pa’bicaranna) during the Mamanu-manu ceremony. Data were collected through observation, non-participatory observation (simak bebas libat cakap), recording, and note-taking techniques. The data were analyzed using qualitative data analysis procedures including data reduction, data display, and conclusion drawing. The results of the study show that there are 24 utterances containing four categories of illocutionary speech acts based on Searle’s (1979) theory, namely assertive, directive, commissive, and expressive speech acts. These speech acts reflect the communicative strategies used by the Bugis community in conveying intentions, requests, commitments, and expressions within the context of traditional marriage negotiations.